1998
DOI: 10.1111/j.1540-8159.1998.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Fast Fourier Transform Analysis of Ventricular Fibrillation Intervals to Predict Ventricular Refractoriness and Its Spatial Dispersion

Abstract: A technique of fast Fourier transform analysis has been used to derive mean ventricular fibrillation (VF) intervals, and to confirm that these VF intervals predict ventricular refractory periods. Twenty episodes of VF were induced by a rapid ventricular pacing in 12 sheep. VF activations in a 10-second period were simultaneously acquired from 64 epicardial sites with an electrode sock. The VF electrograms were analyzed by a fast Fourier transform analysis. The dominant peak frequency of the VF spectrum in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…The significance of disparity in refractoriness in the genesis of tachyarrhythmias has been emphasized by several experimental studies [6,8,9]. In the present study, the dispersion of the 10th percentile VF intervals between the RV apex and posterior LV is markedly larger than the previously reported dispersion of repolarization in patients without malignant ventricular arrhythmias [14,15].…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The significance of disparity in refractoriness in the genesis of tachyarrhythmias has been emphasized by several experimental studies [6,8,9]. In the present study, the dispersion of the 10th percentile VF intervals between the RV apex and posterior LV is markedly larger than the previously reported dispersion of repolarization in patients without malignant ventricular arrhythmias [14,15].…”
Section: Discussioncontrasting
confidence: 51%
“…However, the VERP during VF could not be tested using this technique. Fibrillation intervals have been used as an index of local refractoriness and shown to correlate well with the local atrial and ventricular refractoriness determined using extrastimulus technique in animal [4,6-8] and human subjects [5,9] in serval previous studies. This method is based on the assumption that during fibrillation, cells are reexcited by one of many multiple wavelet as soon as their refractoriness ends and recovers their excitablity.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, frequency blobs can be due to a complex meandering reentrant circuit. Previous studies 5,7,23,35 indicated that the action potential duration (APD) and refractory period at each site influences the VF frequencies and activation intervals recorded from the same site. Hence, conditions that reduce the dispersion of APDs are expected to depress the number of VF frequency blobs because either a single dominant rotor is formed or multiple rotors in different location share the same frequency.…”
Section: Discussionmentioning
confidence: 99%
“…30 The local refractory period influences VF dynamics by limiting the range of VF frequency. 31 The DF of short intervals of induced VF is highly reproducible.…”
Section: Df Reproducibilitymentioning
confidence: 99%